Case Report: Post-mortem Histopathological and Molecular Analyses of the Very First Documented COVID-19-Related Death in Europe - Bogdanović, Milenko; Skadrić, Ivan; Atanasijević, Tatjana; Stojković, Oliver; Popović, Vesna; Savić, Slobodan; Mihailović, Zoran; Radnić, Bojana; Aćimović, Tijana; Damjanjuk, Irina; Despotović, Sanja; Barać, Aleksandra (Frontiers in Medicine, 2021)
In Europe, the first case of coronavirus disease (COVID-19) and the first COVID-19-related death were reported in France on January 24th and February 15th, 2020, respectively. Officially, the first case of COVID-19 infection in the Republic of Serbia was registered on March 6th. Herein, we presented the first case of retrospective detection of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in the post-mortem-obtained vitreous humor (VH), which took place on February 5th, 2020. This is the first death in Europe proven to be caused by COVID-19 by means of post-mortem histopathological and molecular analyses. Based on this finding, it appears that SARS-CoV-2 has been spreading faster and started spreading much earlier than it had been considered and that COVID-19 was probably the cause of the much-reported pneumonia of unknown origin in January and February 2020.